Nutritional and herbal therapies for children and adolescents : a handbook for mental health clinicians - Kapalka, George M. (Practical resources for the mental health professional., 2010)
This volume assists practicing mental health professionals in expanding their knowledge about nutritional and herbal interventions that can be attempted as alternatives to prescription medications. Designed to provide guidance for non-medical caregivers treating children and adolescents who present with emotional and/or behavioral difficulties such as such as depression, anxiety, ADHD, sleep difficulties, impulsivity, distractibility, and other psychological and psychiatric disorders, the volume provides a comprehensive discussion of naturopathic solutions based on existing research. In areas where research is not extensive, conclusions are provided about potentially beneficial effects based on the specific pharmacologic action of the compounds. Dosage for specific age groups, schedules of administration, dietary considerations (i.e., whether or not to take the supplement with food), monitoring for response and adverse effects, signs of dangerous reactions, and the need to control interactions with other compounds (i.e., prescription medications) are thoroughly reviewed with regard to each supplement discussed in the book. Reviews specific psychological disorders (i.e. ADHD, depression, mania, anxiety, sleep difficulties, tic behaviors and autism) and the available data about their treatment with the use of nutritional and herbal supplements. Provides rationale for the use of every specific compound with detailed recommendations tailored for each age group with regard to the dosage, frequency of administration, possible dangers and monitoring for side effects. Discusses claims of efficacy used to market various products and ground those claims within fully vetted scientific research. Discusses neurobiology, pharmacodynamics and pharmokinetics in detailed but accessible language.